PERTIMBANGAN HUKUM MENGENAI NOODWEER SEBAGAI DASAR PEMBELAAN DIRI TERHADAP PSIKOPAT DALAM DELIK PEMBUNUHAN - Yulia, Linda Tri; Soeskandi, Hari (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2022)
The purpose of this research is to find answers and also someone with legal certainty when a person suffering from a psychopath commits noodweer in 49 KUHP which causes death, whether they can be convicted or not. Researchers use normative legal research by taking inventory and reviewing or analyzing secondary data in the form of primary legal materials and secondary legal materials by understanding law as a set of rules or positive norms in the statutory system that regulates human life which aims to find out about the rule of law, legal principles, and legal doctrines which is actually in order to provide an answer and solve problems on the legal issues that being studied. By using that concept that the researcher has created, the researcher also wants to explain the reasons for justification and forgiveness in the abolition of crimes for people with psychopaths and examine the determination of which legal rules are appropriate to be imposed on a psychopaths patient. So as to be able to provide an answer regarding the research study being studied